Proposition of indicators of anthropogenic pressure in the Bay of Toulon (Mediterranean Sea) based on zooplankton time-series. (15th June 2016) - Serranito, B.; Aubert, A.; Stemmann, L.; Rossi, N.; Jamet, J.L.
Abstract: Zooplankton present characteristics of high interest in the frame of investigation for organisms sensitive to environmental changes and/or anthropogenic pressures. Such indicators are particularly needed in the present context of European legislation (Marine Strategy Framework Directive). However, zooplankton have not been given the interest they should have in regards to these issues. The aim of the present study is to provide an attempt of proposition of indicators of good environmental status and associated thresholds based on zooplankton data. Zooplankton time-series (2002–2013) from the Toulon Bay in the Mediterranean was used. This time-series presents the great characteristics that the sampling has be done jointly in two areas of the Bay of Toulon known to differ in term of anthropogenic pressures. The study focus on the copepod assemblage and different potential indicators are tested: ratio of copepod families on total copepod and diversity index (Piélou's evenness). The indicators relevance was evaluated per season by looking at the importance of the overlapping region between density's distributions for each indicator in both bays. This methodology well-recognized is commonly used, particularly in the medical sector, for a long time. The results show that the Oithonidae relative abundance and the Piélou's evenness index are the best indicators of anthropogenic pollution for this case study. Thresholds related to the selected indicators are also proposed in order to characterize the degree of anthropogenic pressure for the Toulon Bay and to provide a first evaluation for potential environmental management. Applicability of the selected indicators and future development needed are also discussed. This study is a first step in the investigation for operational zooplankton indicators and should open the way for additional studies in coastal anthropized area such as the Mediterranean coast where it is more urgently needed. Highlights: Zooplankton indicators of anthropogenic pressure were identified. Oithonidae family based indicator and Piélou's evenness index are most relevant. One specific indicator species dominates the Oithonidae: Oithona nana . Thresholds for the relevant indicators are provided for environmental management.